First Brazilian consensus on the management of localized and locally advanced urothelial bladder cancer: a SBU-SBOC-SBRT-LACOG-GU panel review - Nogueira, Lucas; Carvalho, Icaro Thiago de; Adamy, Ary, Junior; Chade, Daher; Piovesan, Luis Felipe; Favaretto, Ricardo; Borges, Allisson Bruno Barcelos; Accioly, Arthur; Bastos, Diogo Assed; Rosa, Diogo Augusto Rodrigues da; Maluf, Fernando C; Soares, Andrey (Brazilian Journal of Oncology, 2021)
Introduction: Urothelial carcinoma, especially localized bladder cancer, has a substantial prevalence in Brazil with 9,480 new cases each year and 3,903 deaths, therefore progress is required in its management in order to decrease its recurrence and progression, and improve survival. Material and Methods: Medical oncologists, radiation oncologists, and urologists from Brazil conducted a meeting to vote the best approaches available in this country in the diagnosis, staging, and treatment of localized and locally advanced urothelial bladder carcinoma. The panel drew up 73 questions and answers were chosen considering the feasibility according to the access to drugs and the procedures used in this country. Each answer reaching 75% of voters was considered a consensus. The results of this consensus were compared with evidence published in the medical literature and rated with a level of evidence and grade of recommendation using the Oxford classification. Results: Transurethral resection of bladder tumors confirms the diagnosis of and provides initial treatment for non-muscle-invasive bladder cancers. Repeated resection is necessary in selected cases and should not delay further treatment. The use of intravesical Bacillus Calmette-Guérin is performed according to risk stratification, showing a significant reduction in tumor recurrence and progression, and improved disease-specific survival in intermediate- and high-risk patients. Radical cystectomy should be considered for high-progression risk cases after Bacillus Calmette-Guérin treatment failure and for localized muscle-invasive bladder cancer. Conclusion:  Management of urothelial carcinoma often requires a multidisciplinary team with surgical and clinical approaches, based on the expertise of professionals and evidence from the literature.
Keywords: Urinary bladder neoplasms; Cystectomy; Consensus; Carcinoma; Transitional cell; Administration; Intravesical.